ANALISIS KEBERLANJUTAN TANAMAN KELAPA SAWIT PADA LAHAN GAMBUT DI PROVINSI JAMBI - Guna, Adi; Napitupulu, Dompak; Rosyani, Rosyani (Universitas Jambi, 2025)
Oil palm plantations in the peatlands of Jambi Province pose sustainability challenges due to their impact on the environment, especially groundwater depreciation and greenhouse gas emissions. This study aims to analyze the development, sustainability status, and key leverage factors that affect the sustainability of independent oil palm in peatlands. The research was carried out in three districts in Jambi Province using purposive and simple random samplingmethods, with 100 farmers as respondents. The data analysis method was carried out descriptively and quantitatively using the RAP-Palm Oiland Multidimensional Scaling(MDS) models. The results show that the average plant life is 20 years with a productivity of 930 Kg/Ha/Year. The sustainability of oil palm plantations is in the category of quite sustainable with a multidimensional index score of 60.18. The economic dimension recorded the highest score of 78.65, the technology dimension 47.07 and the institutional dimension 48.47. The main leverage factors include peat maturity, selling price of Fresh Fruit Bunches, land ownership status, use of superior seeds, and the existence of field companions. This research provides an important picture for policy-making in improving the sustainability of oil palm inpeatlands. From the results of this study, it gives implications that this research contributes to the achievement of SDG 2 (Zero Hunger), SDG 8 (Decent Work and Economic Growth), SDG 12 (Responsible Consumption and Production), and SDG 15 (Life on Land).However, the low score in institutional and technological aspects shows the need for an integrated strategy to truly support sustainable development so that it is important to strengthen farmer organizations, cooperatives, and the role of field assistantsso that the sustainability of oil palm plantations will be maintained.